Representation of Islam and Hinduism in the Bajrangi Bhaijaan Film Charles Sanders Pierce’s Semiotics Theory - Hanif, Muh.; Rahmadhani, Lutfi Aulia (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2022)
In inter-religious relations there are various ways and steps to promote peace. One way is through audio-visual media in the form of films. The Bajrangi Bhaijaan film, a Bollywood production, has many messages that are closely related to the values that carry a message of peace between religious communities. This article attempts to represent how a good deed can be done regardless of religious background. In particular, this article describes the various behaviors of religious people, in this case Islam and Hinduism, which are represented through the roles played by the characters in the film. The method used in this article is a qualitative-descriptive method using Charles Sanders Pierce's semiotic analysis. The article argues that the various attitudes displayed through the characters played in the film about the relationship between Muslims and Hindus in India and with neighboring countries, namely Pakistan, can be an illustration for religious people to live side by side in harmony.